KEBIJAKAN STABILISASI HARGA MINYAK GORENG - Astari Wirastuti; Hamdani Surachman (Buletin Ilmiah Litbang Perdagangan, 2009)
Generally,   the retail price stability of cooking oil has decreased in the past two years. Cooking oil price shocks hit Indonesia from January 2000 up to December 2007 due to the increase of gasoline price and the fluctuation of CPO price in the international market. The result of this research shows that there are five variables which significantly influence the cooking oil price: CPO international price (in US Dollar), excange rate, export tax, food crisis (dummy variable) a previous cooking oil price. It is r4commended that the  Govermment of Indonesia (GOI) should only focus on the implementation of two policies : progressive export tax and subsidy  for poor people. From the location aspect, GOI should focus its policies in Medan, Jakarta and Makasar. Medan and Jakarta suffers the most frequent price shocks, while Makasar suffers the highest price shocks.